Novel Decellularization Method for Tissue Slices - Narciso, Maria; Ulldemolins, Anna; Júnior, Constança; Otero, Jorge; Navajas, Daniel; Farré, Ramon; Gavara, Núria; Almendros, Isaac (Frontiers in Bioengineering and Biotechnology, 2022)
Decellularization procedures have been developed and optimized for the entire organ or tissue blocks, by either perfusion of decellularizing agents through the tissue’s vasculature or submerging large sections in decellularizing solutions. However, some research aims require the analysis of native as well as decellularized tissue slices side by side, but an optimal protocol has not yet been established to address this need. Thus, the main goal of this work was to develop a fast and efficient decellularization method for tissue slices—with an emphasis on lung—while attached to a glass slide. To this end, different decellularizing agents were compared for their effectiveness in cellular removal while preserving the extracellular matrix. The intensity of DNA staining was taken as an indicator of remaining cells and compared to untreated sections. The presence of collagen, elastin and laminin were quantified using immunostaining and signal quantification. Scaffolds resulting from the optimized protocol were mechanically characterized using atomic force microscopy. Lung scaffolds were recellularized with mesenchymal stromal cells to assess their biocompatibility. Some decellularization agents (CHAPS, triton, and ammonia hydroxide) did not achieve sufficient cell removal. Sodium dodecyl sulfate (SDS) was effective in cell removal (1% remaining DNA signal), but its sharp reduction of elastin signal (only 6% remained) plus lower attachment ratio (32%) singled out sodium deoxycholate (SD) as the optimal treatment for this application (6.5% remaining DNA signal), due to its higher elastin retention (34%) and higher attachment ratio (60%). Laminin and collagen were fully preserved in all treatments. The SD decellularization protocol was also successful for porcine and murine (mice and rat) lungs as well as for other tissues such as the heart, kidney, and bladder. No significant mechanical differences were found before and after sample decellularization. The resulting acellular lung scaffolds were shown to be biocompatible (98% cell survival after 72 h of culture). This novel method to decellularize tissue slices opens up new methodological possibilities to better understand the role of the extracellular matrix in the context of several diseases as well as tissue engineering research and can be easily adapted for scarce samples like clinical biopsies.